Snow Like Ashes : Ice Like Fire - Book 2 - Raasch, Sara (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
When Cordellan debt forces the Winterians to dig their mines for payment, they unearth something powerful and possibly dangerous: Primorias lost chasm of magic. Theron sees this find as an opportunity -- with this much magic, the world can finally stand against threats like Angra. But Meira fears the danger the chasm poses -- the last time the world had access to so much magic, it spawned the Decay.
Keywords: Magic -- Juvenile fiction; Slavery -- Juvenile fiction; Orphans -- Juvenile fiction; Magic -- Fiction; Slavery -- Fiction; Orphans -- Fiction